Research on Flexural Performance of Basalt Fiber-Reinforced Steel–Expanded Polystyrene Foam Concrete Composite Wall Panels - Fang Liu; Long Zhao; Longxin Yuan; Gang Wu; Ran Zheng; Yusong Mu (Buildings)
This paper presents a novel design of prefabricated steel–EPS foam concrete composite wall panels, which can solve issues such as long curing times, decreased impermeability and durability, easy corrosion of steel reinforcement, and difficult construction under the cold climate conditions in Northeast China. A parametric analysis of the composite wallboard was carried out using the finite-element analysis software ABAQUS 6.12. In-depth exploration was conducted on the contributions of parameters such as the density of foam concrete, the strength of cold-formed thin-walled C-section steel, and the cross-sectional height of cold-formed thin-walled C-section steel compared to the overall flexural bearing capacity of the composite wallboard as well as the impacts of these parameters on the failure modes. The mechanical properties of the composite wallboard were verified through four-point bending tests. The bearing capacity of this composite wallboard can reach up to 100.58 kN at most, and its flexural bearing capacity can reach 30.44 kN·m. Meanwhile, its ductility coefficient of 2.9 is also within the optimal range. The research results confirm the superior mechanical properties of the designed composite wallboard, providing beneficial references for the research on similar composite material structures.